2018
DOI: 10.1159/000494590
|View full text |Cite
|
Sign up to set email alerts
|

FGFR2 Promotes Gastric Cancer Progression by Inhibiting the Expression of Thrombospondin4 via PI3K-Akt-Mtor Pathway

Abstract: Background/Aims: Fibroblast growth factor receptor 2 (FGFR2) has attracted considerable interest as a therapeutic target in gastric cancer (GC). There is growing evidence to suggest that the bioavailability of the potent pro-tumor function of FGFR2 is associated with thrombospondins (TSPs). As a follow-on from our previous study, here we evaluated the potential clinical significance and mechanism of the relationship between FGFR2 and TSP4 in GC. Methods: Expression levels of FGFR2 and TSP4 were detected by imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 24 publications
0
32
0
Order By: Relevance
“…Huang et al recently suggested that FGFR2 signaling promotes GC by regulating the expression of Thrombospondin 1 (THBS1) and THBS4 via the PI3K-Akt-mTOR pathway. They indicated that FGF7-FGFR2 signaling upregulates THBS1, while THBS4 is decreased by the FGFR2-Akt cascade [80,89]. These studies established that PI3K-Akt signaling partially contributes to the tumor-promoting function of FGFR2 in GC, although the contribution of the THBS family to GC is still not fully understood.…”
Section: Deregulation Of the Fgf-fgfr Signaling In Gastric Carcinomentioning
confidence: 99%
“…Huang et al recently suggested that FGFR2 signaling promotes GC by regulating the expression of Thrombospondin 1 (THBS1) and THBS4 via the PI3K-Akt-mTOR pathway. They indicated that FGF7-FGFR2 signaling upregulates THBS1, while THBS4 is decreased by the FGFR2-Akt cascade [80,89]. These studies established that PI3K-Akt signaling partially contributes to the tumor-promoting function of FGFR2 in GC, although the contribution of the THBS family to GC is still not fully understood.…”
Section: Deregulation Of the Fgf-fgfr Signaling In Gastric Carcinomentioning
confidence: 99%
“…Some of the 12 functional genes have been connected with COAD or other diseases according to the existing research. For example, TPM2 was reported to be in implicated in CRC [ 60 ]; STMN2 might be involved in beta-catenin/TCF-mediated carcinogenesis in human hepatoma cells [ 61 ]; CHMP4C was identified as a novel molecular target gene for ovarian cancer [ 62 ]; GRIA3 may act as a mediator of tumor progression in pancreatic cancer [ 63 ]; WDR1 was reported as a therapeutic target in lung cancer [ 64 ]; CPT2 was identified as a potential diagnostic biomarker of colon cancer [ 65 ]; Somatic deletion of KDM1A plays role in advanced colorectal cancer stages [ 66 ]; NFE2L1 , also called Nrf1, was found to be associated to high-risk diffuse large B cell lymphoma [ 67 ]; Gatza et al reported that TGFBR3 promotes colon cancer progression [ 68 ]; FGFR2 was shown to promote gastric cancer progression [ 69 ]. Therefore, the 12 functional genes probably play important roles in COAD and could be the potential prognosis biomarkers for COAD.…”
Section: Discussionmentioning
confidence: 99%
“…The AKT signaling pathway is one of the most common proliferation pathways in many cancers [37]. It is well known that dysregulation of the AKT signaling pathway is refered to tumorigenesis and progression, such as liver, lung, breast, thyroid, prostate, bladder, pancreatic, gastric, colorectal and cervical cancers [38,39]. It is reported that the various clinicopathological characteristics of cancers are closely related to the activation of AKT signaling pathway [40].…”
Section: Discussionmentioning
confidence: 99%